2021
DOI: 10.3390/toxins13080552
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Enrichment Cultures Biotransform the Mycotoxin Deoxynivalenol into a Novel Metabolite Toxic to Plant and Porcine Cells

Abstract: The mycotoxin deoxynivalenol (DON), produced in wheat, barley and maize by Fusarium graminearum and Fusarium culmorum, is threatening the health of humans and animals. With its worldwide high incidence in food and feed, mitigation strategies are needed to detoxify DON, maintaining the nutritional value and palatability of decontaminated commodities. A promising technique is biological degradation, where microorganisms are used to biotransform mycotoxins into less toxic metabolites. In this study, bacterial enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…It is unclear how these isolates interact with the fungus, but it has recently been reported that bacteria could be able to influence the mycotoxin biosynthesis by inhibiting Tri -gene expression [ 65 ]. Moreover, some bacterial taxa are known to metabolize DON [ 66 ]. Lastly, interaction with the plant defense mechanism also has the potential to reduce disease pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how these isolates interact with the fungus, but it has recently been reported that bacteria could be able to influence the mycotoxin biosynthesis by inhibiting Tri -gene expression [ 65 ]. Moreover, some bacterial taxa are known to metabolize DON [ 66 ]. Lastly, interaction with the plant defense mechanism also has the potential to reduce disease pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial enrichment cultures that included Cephaloticoccus spp. have been used to biotransform mycotoxin deoxynivalenol into less toxic metabolites [38]. Chitinophaga spp.…”
Section: The Bacterial Communities Involved In the Bde-209 Biodegrada...mentioning
confidence: 99%